2011
DOI: 10.1186/1752-1947-5-338
|View full text |Cite
|
Sign up to set email alerts
|

Purtscher-like retinopathy following valsalva maneuver effect: case report

Abstract: IntroductionPurtscher's retinopathy is a rare condition that is noted in cases related to various types of trauma. The characteristic finding in the fundus is the presence of multiple Purtscher flecken. Purtscher-like retinopathy has a similar presentation in the fundus, but without an association with trauma.Case presentationA 43-year old Malay man presented with a sudden onset of central foggy vision in the left eye after holding his breath for two minutes while catching a falling object. It was not associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The funduscopic findings include whitening of the retina, multiple cotton wool spots, and bleeding of different sizes. The retinal changes are explained by acute ischemia [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The funduscopic findings include whitening of the retina, multiple cotton wool spots, and bleeding of different sizes. The retinal changes are explained by acute ischemia [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 There are no specific recommended guide lines for treatment of patients with Purtscher's Retinopathy. Saidin Nor-Mosniwati et al 9 reported a case who was treated with indomethacin tablets 25 mg daily for six weeks and his vision improved from finger counting at presentation to 6/12. Wang et al reported a case of patient who was given a mega dose of steroid that showed a good visual response with in first two weeks of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…5 Although there are publications on the use of megadose steroid therapy, hyperbaric oxygen therapy, and oral indomethacin in treatment, they do not provide sufficient evidence for a disease that can be self-limiting. 9 While the benefit of intravitreal bevacizumab was reported in the treatment of macular edema associated with Purtscher-like retinopathy, the complete regression of macular edema at 3 months after injection raised questions about its effectiveness. 10…”
Section: Discussionmentioning
confidence: 99%